Public information campaign on aflatoxin contamination of maize grains in market stores in Benin, Ghana and Togo - James, B.; Adda, C.; Cardwell, K.; Annang, D.; Hell, K.; Korie, S.; Edorh, M.; Gbeassor, F.; Nagatey, K.; Houenou, G. (2007)
Rotary International with the International Institute of Tropical Agriculture (IITA) conducted an information campaign from 2000 to 2004 to increase public awareness of aflatoxin in Benin, Ghana and Togo. Key informant interviews with 2416 respondents showed poor baseline knowledge of aflatoxin and its health risks. The campaign included monitoring of aflatoxin contamination in maize grains from market stores in 38 cities and towns. Aflatoxin concentration in contaminated samples ranged from 24 to 117.5 ng g−1 in Benin, from 0.4 to 490.6 ng g−1 in Ghana, and from 0.7 to 108.8 ng g−1 in Togo. The campaign significantly increased public awareness that populations were exposed to high levels of aflatoxin. The number of maize traders who were informed about the toxin increased 10.3 and 3.2 times in Togo and Benin, respectively; at least 33% more traders believed the information in each of Benin and Togo; 11.4 and 28.4% more consumers sorted out and discarded bad grains in Benin and Ghana, respectively. This paper concludes that sustained public education can help reduce aflatoxin contamination.